Biology of Nicotiana glutinosa L., a newly recorded species from an archaeological excavation site in Egypt - Selim Z. Heneidy; Yassin M. Al-Sodany; Amal M. Fakhry; Sania A. Kamal; Marwa Waseem A. Halmy; Laila M. Bidak; Eman T. El kenany; Soliman M. Toto (BMC Plant Biology, 2024)
Abstract Background During a field survey of urban flora in Alexandria city in 2019–2022, an interesting species belonging to the Solanaceae was collected from a newly archaeological excavation site and identified as Nicotiana glutinosa L. Many visits were made to the herbaria of Egypt to confirm the species records, but no single record was found. Reviewing the available literature revealed that this tropical American taxon was never recorded in the flora of Egypt. Aims The present study was focused on N. glutinosa growth structure and plant macro- and micromorphology. Methods Ten sampling sites were covered for N. glutinosa size structure. Plant samples were examined for stem anatomy, leaf, seed, and pollen morphology. Results The species size structure reveals that the individual size index ranges from 1.33 to 150 cm, while its density ranges from 4 to 273 individuals /100 m−2. N. glutinosa has successfully established itself in one of the archaeological sites in Egypt, showing a “healthy” population with a high degree of size inequality, characterized by a relative majority of the juvenile individuals. Voucher specimens were deposited in the Herbarium of Alexandria University (ALEX) Faculty of Science, another specimen is processed to make herbarium specimens at the Herbarium of the Botanic Garden (Heneidy et al. collection, deposition number. 5502). Conclusions From our observations, N. glutinosa seems to have invasive potential, as it shows characteristics shared by most invasive species that are thought to help in their successful establishment in new habitats. This article emphasizes the importance of monitoring and regularly reporting the threats of alien invasive species to avoid any possible negative impacts on indigenous biodiversity in the future.